Intrathecal Contrast-Enhanced Magnetic Resonance Imaging of Cerebrospinal Fluid Dynamics and Glymphatic Enhancement in Idiopathic Normal Pressure Hydrocephalus - Eide, Per Kristian; Lashkarivand, Aslan; Hagen-Kersten, Åsmund Aleksander; Gjertsen, Øivind; Nedregaard, Bård; Sletteberg, Ruth; Løvland, Grethe; Vatnehol, Svein Are Sirirud; Pripp, Are Hugo; Valnes, Lars Magnus; Ringstad, Geir (Frontiers in Neurology, 2022)
Idiopathic normal pressure hydrocephalus (iNPH) is a neurodegenerative disease, characterized by cerebrospinal fluid (CSF) flow disturbance. Today, the only available treatment is CSF diversion surgery (shunt surgery). While traditional imaging biomarkers typically assess CSF space anatomy, recently introduced imaging biomarkers of CSF dynamics and glymphatic enhancement, provide imaging of CSF dynamics and thereby more specifically reveal elements of the underlying pathophysiology. The biomarkers address CSF ventricular reflux grade as well as glymphatic enhancement and derive from intrathecal contrast-enhanced MRI. However, the contrast agent serving as CSF tracer is administered off-label. In medicine, the introduction of new diagnostic or therapeutic methods must consider the balance between risk and benefit. To this end, we performed a prospective observational study of 95 patients with iNPH, comparing different intrathecal doses of the MRI contrast agent gadobutrol (0.10, 0.25, and 0.50 mmol, respectively), aiming at the lowest reasonable dose needed to retrieve diagnostic information about the novel MRI biomarkers. The present observations disclosed a dose-dependent enrichment of subarachnoid CSF spaces (cisterna magna, vertex, and velum interpositum) with dose-dependent ventricular reflux of tracer in iNPH, as well as dose-dependent glymphatic tracer enrichment. The association between tracer enrichment in CSF and parenchymal compartments were as well dose-related. Intrathecal gadobutrol in a dose of 0.25 mmol, but not 0.10 mmol, was at 1.5T MRI considered sufficient for imaging altered CSF dynamics and glymphatic enhancement in iNPH, even though 3T MRI provided better sensitivity. Tracer enrichment in CSF at the vertex and within the cerebral cortex and subcortical white matter was deemed too low for maintaining diagnostic information from a dose of 0.10 mmol. We conclude that reducing the intrathecal dose of gadobutrol from 0.50 to 0.25 mmol gadobutrol improves the safety margin while maintaining the necessary diagnostic information about disturbed CSF homeostasis and glymphatic failure in iNPH.